Faktor-Faktor yang Berhubungan Dengan Kejadian Stunting pada Anak Usia Dini di Wilayah Kerja Puskesmas Buhit Kecamatan Pangururan Kabupaten Samosir Tahun 2024 - Sinurat , Arni Wetty; Manurung , Kesaktian; Sembiring, Rinawati; Rochadi, Kintoko; Sinaga, Janno (Journal of Pharmaceutical and Sciences, 2025)
Background: Stunting is a health problem resulting from chronic malnutrition over a long period. Although it serves as the district capital, Pangururan Sub-District still has a relatively high stunting prevalence, with 154 out of 2,460 measured toddlers (6.26%) affected. Identifying associated factors is necessary to design targeted interventions. Objective: This study aims to analyse the factors associated with the incidence of stunting in early childhood children in the working area of Buhit Community Health Centre, Pangururan Sub-District, Samosir Regency. Methods: This study used a cross-sectional design conducted in the working area of Buhit Community Health Centre. The study population consisted of mothers with toddlers in the area, with a sample size of 96 mothers selected using accidental sampling. Data were collected through questionnaires and anthropometric measurements and analysed using the Chi-Square test and logistic regression. Results: Bivariate analysis results showed significant relationships between maternal nutritional status (p=0.000), parenting patterns (p=0.000), maternal education level (p=0.000), family income level (p=0.003), and exclusive breastfeeding (p=0.029) with the incidence of stunting. Multivariate analysis indicated that maternal education level was the most dominant variable (p=0.013; OR=12.814), meaning that mothers with low education levels had a 12.8 times higher risk of having stunted children. Conclusion: Maternal nutritional status, parenting patterns, maternal education, family income, and exclusive breastfeeding were significantly associated with stunting, with maternal education level being the dominant factor. Therefore, stunting prevention efforts in this region should prioritise health education targeting mothers with low educational backgrounds.